Effects of partial sleep restriction and subsequent daytime napping on prolonged exertional heat strain. Issue 7 (23rd April 2015) - Tokizawa, Ken; Sawada, Shin-ichi; Tai, Tetsuo; Lu, Jian; Oka, Tatsuo; Yasuda, Akinori; Takahashi, Masaya
Abstract : Objectives: It is considered that sleep restriction is one of the risk factors for the development of exertional heat stroke and illness. However, how sleep restriction affects exertional heat strain and the nature of the coping strategy involved in this phenomenon remain unclear. Methods: Fourteen healthy subjects were studied on four occasions: after a night of normal sleep (NS, 7–8 h) and after a night of partial sleep restriction (PSR, 4 h), each with or without taking a daytime nap during the subsequent experimental day. The laboratory test consisted of two 40 min periods of moderate walking in a hot room in the morning and the afternoon. Results: The increase in rectal temperature during walking was significantly greater in PSR than in NS in the afternoon. The rating scores for physical and psychological fatigue and sleepiness were significantly greater in PSR than in NS, both in the morning and in the afternoon. The reaction times and lapses in the psychomotor vigilance task (PVT) after walking were significantly worse in PSR than in NS in the morning and after lunch. The nap intervention attenuated significantly the scores for fatigue and sleepiness in PSR. Furthermore, the decreased PVT response in PSR was significantly reversed by the nap. Conclusions: These results suggest that PSR augments physiological and psychological strain and reduces vigilance in the heat. Taking a nap seemed to be effective in reducing psychological strain and inhibiting the decrease in vigilance.